Epigenetic Regulation of β Cell Identity and Dysfunction - Sun, Xiaoqiang; Wang, Liu; Obayomi, S. M. Bukola; Wei, Zong (Frontiers in Endocrinology, 2021)
Beta cell dysfunction and failure are driving forces of type 2 diabetes mellitus (T2DM) pathogenesis. Investigating the underlying mechanisms of beta cell dysfunction may provide novel targets for the development of next generation therapy for T2DM. Epigenetics is the study of gene expression changes that do not involve DNA sequence changes, including DNA methylation, histone modification, and non-coding RNAs. Specific epigenetic signatures at all levels, including DNA methylation, chromatin accessibility, histone modification, and non-coding RNA, define  cell identity during embryonic development, postnatal maturation, and maintain beta cell function at homeostatic states. During progression of T2DM, overnutrition, inflammation, and other types of stress collaboratively disrupt the homeostatic epigenetic signatures in beta cells. Dysregulated epigenetic signatures, and the associating transcriptional outputs, lead to the dysfunction and eventual loss of beta cells. In this review, we will summarize recent discoveries of the establishment and disruption of  cell epigenetic identity, and discuss the potential implication in therapeutic development.